Enhanced Depth Imaging Features of a Choroidal Macrovessel - Choudhry, Netan (Retin Cases Brief Rep, 2016)
PURPOSE: To report a case of a choroidal macrovessel imaged using enhanced-depth imaging spectral domain optical coherence tomorgraphy (EDI SD-OCT) and describe the choroidal features. METHODS: Case report. A 42-year-old man presented with metamorphopsia. Multimodal imaging, including color fundus photography, near infrared reflectance (NIR), and EDI-OCT was used to describe a choroidal macrovessel. RESULTS: Initial ophthalmic examination revealed a serpentine-shaped subretinal pattern deep to the retina near the fovea. When the color image was subjected to a red-filter, a large diameter vessel could be seen coursing from the fovea to the temporal macula. EDI-OCT of the choroidal macrovessel revealed a thickened choroid, and mild deformation of both the ellipsoid zone and the choroidal-scleral junction. En face SD-OCT at the level of the choroid demonstrated the anomalous vessel. CONCLUSIONS: EDI-OCT and en face OCT, used in conjunction with other imaging modalities, can be used to demonstrate the presence and pattern of a choroidal macrovessel. A thickened choroid and overlying outer retinal indentation was observed in association of the choroidal macrovessel. These imaging tools can help distinguish this condition from other diagnoses with a similar appearance, such as ophthalmomyiasis.